Faktor-Faktor Yang Mempengaruhi Initial Return 1 Hari, Return 1 bulan, dan Pengaruh Terhadap Return 1 Tahun Setelah IPO - Emilia Emilia; Lucky Sulaiman; Roy Sembel (Journal of Applied Finance & Accounting, 2008)
There are some anomalies happenning when the shares are traded in the secondary market or stock exchange. When the shares price at the secondary market is higher than the primary market, then we say that there is a positive initial return or underpricing happened. The opposite is negative initial return or overpricing. The purpose of this research is to to study whether the underwriter’s reputation, auditor’s reputation, value of the share offering, percentage of the share offering, and earnings per share towards the IPO price influence the one day initial return, one month return, and one year return after the IPO. The objects of the research are 92 companies that went public through the Jakarta stock exchange market during 1999-2005 that had either positive or negative initial return. This research is done using multiple regression analysis with F Test, t Test, R2 Test, and classic assumption testing. The result indicates that only the value of the share offering variable that significantly influence the one day initial return and one month initial return negatively. For the one year return regression model, only the one month return that significantly influence the return one year after the IPO positively. It can be concluded that the higher the value of the share offering the smaller the one day initial return and one month initial return will be, and thus minimizing the positive initial return. Furthermore, the higher the one month initial return the higher also the one year return after the IPO.